(untitled) (Journal of Educational Management, 2023)
Abstract Continuous professional development is the heartbeat of today’s tertiary education economy. It is the hallmark of performance in the continuous mission of improvement of national education and dynamism in the worldwide knowledge economy and management. This has led to the discourse of college education and CPD relevance in the accomplishment of production of high-quality teachers for the implementation of basic education in our country Ghana, making the theme an important topic for all stakeholders. This research was therefore conducted in 2017 to unearth the relative importance attached to the subject matter by tutors and administrators of some selected Volta Region Colleges of Education. The study was qualitative with a case study design that gathered data from 4 principals through semi-structured interviews and open-ended questions used on 4 vice principals and 12 tutors. The human coder system was employed under thematic analysis. In the findings, benefits of continuous professional development were capacity building, promotion in career, and improving learning outcomes of student teachers among others. The conclusion was drawn that the colleges needed to institute continuous professional development on departmental bases and own it as part of their internal academic and professional practice to help them nurture the faculty better as a means of safeguarding the profession, professional, public, and employer. Recommended that College Management should include college-based departmentalised CPD on their institution-wide academic programmes and budget for implementation to ensure effective execution of CPD activities in all the academic departments of the colleges. Keywords: Continuous Professional Development, Academic Staff, College of Education, Learning Outcome.